Production of Instagramable Content to Create a Tourist Market at the Toba Caldera Pilot Tourism Site: Parsingguran II Village, Pollung District, Humbang Hasundutan Regency National Tourism Strategic Area - Sinulingga, Samerdanta; Lubis, Suwardi; Pohan, Riko Andika Rahmat (Universitas Negeri Medan, 2023)
Creating Instagramable content is a highly supported part of the strategic plan of the Ministry of Tourism of the Republic of Indonesia for the development of the tourism sector, especially the super-priority area of the Toba Caldera KSPN. One of the areas that received the highest attention was Parsingguran II Village, Pollung District, Humbang Hasundutan Regency. Examining the advantages of this village are 1) The village with the fastest development of tourism facilities in Humbang Hasundutan District; 2) Selected as one of the villages that received a visit from the President of the Republic of Indonesia, Ir. H. Joko Widodo and were awarded 3 Belgian Blue cows imported from Belgium; 3) Becoming one of the beneficiary villages for the food estate megaproject. These three things illustrate indicators that this village must be supported by various parties in developing the agricultural and tourism sectors in the future as a World Class Destination. This development process certainly does not escape from the main problems, one of which is the very weak index of resources in the field of tourism marketing. With the massive development in Parsingguran II village, this village should have stepped into the next stage, namely opening the door for tourist visits to its area. The location of urgency of this service is so that the government budget that has been given can be balanced with an increase in the human resource index that will be carried out in this community service program. The HR development index offered is the Production of Instagramable Content to Create a Tourist Market at the Toba Caldera Pilot Tourism Site with the ultimate goal of creating an economic cycle that benefits the community. The objectives of this activity are 1) To create technical visual content to attract tourist visits, because tourism development without the presence of tourists is a fatal mistake in organizing tourism; 2) to improve the quality of village human resources so that they have the ability in the field of promotion using visual tools and managing social media so that they can attract tourist arrivals. The outputs in this community service are sinta-accredited national journals, articles in the mass media, activity videos, and HKI as additional outputs.